(untitled) (INTERNATIONAL JOURNAL OF INDUSTRIAL AND PRODUCTION ENGINEERING, 2025)
Turbo pumps are extensively employed in ships for transporting fluids of varying properties due to their simple design, low maintenance, and ability to handle large fluid efficiently. However, varying operational conditions can significantly affect their performance with factors such as attrition, low head pressure, mechanical losses with reducing efficiency and increasing energy consumption. Allowing turbo pumps (centrifugal type) to operate under any of those mentioned factors could result to early equipment failure. This study specifically addresses the pumps performance with reference to head pressure, flow and efficiency limitations through component resizing which integrate experimental evaluation with theoretical modeling. Experimental testing assessed the real-world performance characteristics of an existing pump using a compact TQH47 pump demonstration unit, while theoretical resizing and computational modeling optimized the pump design parameters for an improved performance. The analysis highlights the critical influence of pump geometry including inlet and outlet ports, blade angles, and the spiral/volute chamber on performance. Computational fluid dynamics analysis in SolidWorks fluent simulation demonstrated that the resized pump achieved a substantial improvement against the actual pump, with efficiency improved by 9.4% from 50% to 59.4% (9.4% higher than the actual pump), head pressure improved by 14m from 24 m to 38 m (recorded 14m increment), and the flow rate improved by 0.1176 from 0.00455 to 0.122241.